Interferon Receptor Signaling Pathways Regulating PD-L1 and PD-L2 Expression - Garcia-Diaz, Angel; Shin, Daniel Sanghoon; Moreno, Blanca Homet; Saco, Justin; Escuin-Ordinas, Helena; Rodriguez, Gabriel Abril; Zaretsky, Jesse M.; Sun, Lu; Hugo, Willy; Wang, Xiaoyan; Parisi, Giulia; Saus, Cristina Puig; et al. (Cell reports (Cambridge), 2017)
PD-L1 and PD-L2 are ligands for the PD-1 immune inhibiting checkpoint that can be induced in tumors by interferon exposure, leading to immune evasion. This process is important for immunotherapy based on PD-1 blockade. We examined the specific molecules involved in interferon-induced signaling that regulates PD-L1 and PD-L2 expression in melanoma cells. These studies revealed that the interferon-gamma-JAK1/JAK2-STAT1/STAT2/STAT3-IRF1 axis primarily regulates PD-L1 expression, with IRF1 binding to its promoter. PD-L2 responded equally to interferon beta and gamma and is regulated through both IRF1 and STAT3, which bind to the PD-L2 promoter. Analysis of biopsy specimens from patients with melanoma confirmed interferon signature enrichment and upregulation of gene targets for STAT1/STAT2/STAT3 and IRF1 in anti-PD-1-responding tumors. Therefore, these studies map the signaling pathway of interferon-gamma-inducible PD-1 ligand expression. [Display omitted] •PD-L1 is primarily regulated by interferon gamma signaling in melanoma cells•PD-L2 is regulated by both interferon beta and gamma signaling•Regulation of PD-1 ligands works mainly through the JAK1/2-STAT1/3-IRF1 axis Garcia-Diaz et al. performed a small hairpin RNA screen and genetic and functional studies to map the signaling pathways that result in reactive PD-L1 and PD-L2 on melanoma cells upon interferon gamma exposure. The authors highlight the importance of the JAK1/JAK2-STAT1/STAT2/STAT3-IRF1 axis for clinical responses to PD-1 blockade therapy.